Balancing the risks: continuous vs. interrupted anticoagulation during TAVI – what does the evidence say? - Ravi Patel; Emmanuel Kokori; Gbolahan Olatunji; Israel Charles Abraham; Adeola Akinboade; Emmanuel Ababio Agyemang; Adetola Babalola; Nicholas Aderinto (Thrombosis Journal)
Abstract Anticoagulation therapy is a critical component of post-transcatheter aortic valve implantation (TAVI) management, aimed at reducing the risk of thromboembolic events and mortality. This review examines the efficacy of continuous versus interrupted anticoagulation strategies in TAVI patients, focusing on mortality, stroke rates, and composite events. A literature review was conducted, analyzing recent studies that evaluate the impact of different anticoagulation regimens on clinical outcomes in TAVI patients. Key outcomes assessed include all-cause mortality, thromboembolic events, and major cardiovascular complications within 30 days and up to one year post-procedure. The review identifies a trend favoring continuous anticoagulation, particularly with direct-acting oral anticoagulants (DOACs), which was associated with lower mortality rates and reduced stroke incidence in high-risk patients. However, findings were inconsistent across studies, with some reporting no significant differences in outcomes between continuous and interrupted strategies. Additionally, the review highlights the need to balance the benefits of thromboembolic prevention with the increased risk of bleeding and vascular complications associated with continuous therapy. The findings show the importance of individualized anticoagulation strategies tailored to patient risk profiles. Clinicians should weigh the potential benefits of continuous anticoagulation against the risks, particularly in high-risk populations. Ongoing research is essential to refine anticoagulation protocols in TAVI patients, enhancing both safety and efficacy in clinical practice.